Implication of Serum and Salivary Levels of Albumin as a Diagnostic Tool in Oral Premalignancy and Malignancy - Sinha, Riti Tushar Kanti (Annals of Pathology and Laboratory Medicine, 2020)
Background: Reactive oxygen and nitrogen species are involved in the initiation and promotion of the multistep carcinogenesis. In neoplastic conditions many biochemical substances many biochemical substances including albumin show altered values .The aim of the present study was to investigate whether serum and salivary albumin levels can be used as diagnostic tools in oral premalignant and malignant leisons. Methods: The study includes a total of 45 subjects with 15 each of normal healthy, pre-malignancy and malignancy. Five milliliter of venous blood was drawn and unstimulated saliva was collected in the early morning. Albumin levels were estimated by Bromocresol Green Method. Results: Serum albumin levels were found to decrease in pre-malignancy and malignancy as compared to healthy individuals. Salivary Albumin levels were increased in pre-malignancy and malignancy as compared to healthy individuals. Conclusion: Tobacco consumption is one of the most important risk factors for the development of oral cancer. Burst of reactive oxygen species which cause oxidative stress in tobacco users is prime form of damage brought to the genetic material leading to non-lethal mutations causing pre-malignancy and malignancy. Serum protein has long been implicated to have anti-oxidant properties due to rich concentration of free thiol group. Albumin is a potent extracellular anti oxidant defense and a reliable marker of oxidative stress in the body. It could be helpful in the early identification of various oral pre malignancy and malignant leisons.